ANALISIS VIBRASI SEBAGAI INDIKATOR KINERJA OPTIMAL PADA POMPA SENTRIFUGAL (X 123 Z) - Musad, Bariq Nashir; Golwa, G.V.; Azmi, M.R.H.A.; Dwiyanto, R.F.; Kuswantoro, H.; Nafi, I.M. (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Vibration in operating machines can cause damage and failure to machine components. However, this damage can be detected and analyzed using predictive maintenance methods, such as vibration monitoring with a single channel data collector. This study aims to analyze the optimal performance indicators in centrifugal pumps using an vibration analysis method where vibration data will be collected on centrifugal pumps with Vib Expert II tools which will be spectrally analyzed to identify dominant frequencies and unusual vibration patterns. The vibration measurement results are compared with the tolerance limits specified by the ISO 10816-3 standard. The results show that the vibration values at all measurement points are below the tolerance limit. The vibration trend is also stable and does not show any significant changes. Based on the vibration measurement results, it can be concluded that the centrifugal pump is in normal condition. This indicates that the pump is operating properly and there is no damage to the pump components.